2017
DOI: 10.1016/j.rboe.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Posterior sacroiliac osteotomy: an alternative to the ilioinguinal approach for pelvic reconstruction in misalignment lesions

Abstract: Pelvic ring fractures occur in association with potentially fatal lesions, whose treatment is a priority in the polytrauma setting. As consequence, the definitive orthopedic approach may be postponed, leading patients to chronic and potentially disabling deformities. The treatment of these deformities is a challenge, requiring highly complex and staged surgical reconstructions. The ilioinguinal approach has been widely used in these surgeries, because it allows the release and mobilization of the hemipelvis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been reported that there was a significant difference in incision length between the lateral rectus abdominis approach and the modified Stoppa approach. [16][17][18] Meanwhile, the operation time and intraoperative blood loss of patients with surgery through the lateral rectus abdominis approach were significantly less than those with modified Stoppa approach. 19 In our study, the observation group showed shorter incision length and less amount of intraoperative blood loss than those of the control group, with statistically significant differences (p<0.05).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that there was a significant difference in incision length between the lateral rectus abdominis approach and the modified Stoppa approach. [16][17][18] Meanwhile, the operation time and intraoperative blood loss of patients with surgery through the lateral rectus abdominis approach were significantly less than those with modified Stoppa approach. 19 In our study, the observation group showed shorter incision length and less amount of intraoperative blood loss than those of the control group, with statistically significant differences (p<0.05).…”
Section: Discussionmentioning
confidence: 97%